The Role of von Willebrand Factor, ADAMTS13, and Cerebral Artery Thrombus Composition in Patient Outcome Following Mechanical Thrombectomy for Acute Ischemic Stroke - Prochazka, Vaclav; Jonszta, Tomas; Czerny, Daniel; Krajca, Jan; Roubec, Martin; Macak, Jirka; Kovar, Petr; Kovarova, Petra; Pulcer, Martin; Zoubkova, Renata; Lochman, Ivo; Svachova, Veronika; et al. (Medical science monitor, 2018)
BACKGROUND The aim of the study was to investigate the role of von Willebrand factor (vWF), the vWF-cleaving protease, ADAMTS13, the composition of thrombus, and patient outcome following mechanical cerebral artery thrombectomy in patients with acute ischemic stroke. MATERIAL AND METHODS A prospective cohort study included 131 patients with ischemic stroke (<6 hours) with or without intravenous thrombolysis. Interventional procedure parameters, hemocoagulation markers, vWF, ADAMTS13, and histological examination of the extracted thrombi were performed. The National Institutes of Health Stroke Scale (NIHSS) score was used on hospital admission, after 24 hours, at day 7; the three-month modified Rankin Scale score was used. RESULTS Mechanical thrombectomy resulted in a Treatment in Cerebral Ischemia (TICI) score of 2-3, with recanalization in 89% of patients. Intravenous thrombolysis was used in 101 (78%). Patients with and without intravenous thrombolysis therapy had a good clinical outcome (score 0-2) in 47% of cases (P=0.459) using the three-month modified Rankin Scale. Patients with a National Institutes of Health Stroke Scale (NIHSS) score ≥15 had significantly increased vWF levels (P=0.003), and a significantly increased vWF: ADAMTS13 ratio (P=0.038) on hospital admission. Significant correlation coefficients were found for plasma vWF and thrombo-embolus vWF (r=0.32), platelet (r=0.24), and fibrin (r=0.26) levels. In the removed thrombus, vWF levels were significantly correlated with platelet count (r=0.53), CD31-positive cells (r=0.38), and fibrin (r=0.48). CONCLUSIONS In patients with acute ischemic stroke, mechanical cerebral artery thrombectomy resulted in a good clinical outcome in 47% of cases, with and without intravenous thrombolysis therapy.
Keywords: Demography; arteriae cerebrales; ischemie mozku; Brain Ischemia; Humans; lidé středního věku; Stroke; Female; Aged; Inflammation; Cerebral Arteries; výsledek terapie; senioři; protein ADAMTS13; lidé; Thrombosis; zánět; hemokoagulace; Thrombectomy; cévní mozková příhoda; trombektomie; ženské pohlaví; ADAMTS13 Protein; Male; Middle Aged; Blood Coagulation; Treatment Outcome; Aged, 80 and over; von Willebrandův faktor; trombóza; demografie; senioři nad 80 let; mužské pohlaví; von Willebrand Factor